Can you teach a hands-on skill online? A scoping review of e-learning for point-of-care ultrasound in medical education - Harel-Sterling, Maya (Canadian Medical Education Journal, 2023)
Background: There is an increasing need and interest in teaching point-of-care ultrasound (POCUS) online. The objective of this study was to systematically review the literature regarding e-learning as a method for teaching POCUS in medical education, to assess the benefits and limitations of various styles of e-learning for POCUS, and to identify gaps in the literature that could help guide future research in this field. Methods: A literature search was conducted on three databases including MEDLINE (Ovid), EMBASE and Cochrane Central Register of Controlled Clinical Trials on October 12, 2021, retrieving a total of 1630 studies. 31 studies met the inclusion and exclusion criteria. These studies were separated into different styles of e-learning and learner outcomes were analyzed based on Kirkpatrick’s hierarchy. Results: The studies were categorized into 3 styles of e-learning: a) blended learning b) online-only (asynchronous or synchronous) and c) use of handheld machines or telesonography. POCUS knowledge and image interpretation were successfully taught online, however online-only learning for image acquisition was not as consistently effective. Blended learning and telesonography were beneficial for learning image acquisition skills. Generally, novice learners benefited most from e-learning. Conclusion: E-learning for POCUS is gaining in popularity in recent years. POCUS is a complex technical skill, and depending on the individual task being taught, different styles of e-learning may be more successful. These findings can inform future POCUS educational programs.